3x+-1=2x

Simple and best practice solution for 3x+-1=2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+-1=2x equation:


Simplifying
3x + -1 = 2x

Reorder the terms:
-1 + 3x = 2x

Solving
-1 + 3x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-1 + 3x + -2x = 2x + -2x

Combine like terms: 3x + -2x = 1x
-1 + 1x = 2x + -2x

Combine like terms: 2x + -2x = 0
-1 + 1x = 0

Add '1' to each side of the equation.
-1 + 1 + 1x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 1x = 0 + 1
1x = 0 + 1

Combine like terms: 0 + 1 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| (x+2)/4=2x/3-1 | | 6a-7=29 | | 3x/8=0 | | 3x+b=2x | | 8(y-4)=-2(8+7) | | m+6=18 | | 5-6(x-4)=-(6-x) | | c/100=51/60 | | 7y-7-4y=4y-1 | | 8a-6=3a+29 | | 6/8=15/4 | | (4/x+3)^-1 | | -1/5=x+2/5 | | (4x/9)^-3 | | 0.1*4200(23-18)/0.435(92-23)= | | 1/2(2x+4)+4x=4(9x/2+3x/4) | | 5(3x-2)+1-3(2x+1)=2(x+1) | | 25x+17=192 | | 28x=8*42 | | 7x+7=4x+58/7 | | (29b-1)-7(4b+3)=-7 | | 54-6c= | | -9z-5=-95 | | 10x+38=188 | | 17+5x=19+x | | 2(x+2)=2x-9 | | 4/5+z=3/4 | | 11+4(3x-1)=5(2x+1)+2(2x-5) | | 49x^2-42x+2=0 | | 12x^2+x+5=8 | | 12-y=2y+3 | | 4y=-8x-8 |

Equations solver categories